A study on demographic and clinicopathological characteristics of severe acute pancreatitis in a tertiary-level intensive care unit in Nepal - Khanal, Kishor; Poudel, Saroj; Ghimire, Anup; Regmi, Ashim; Khadka, Bikash; Bist, Manoj; Shrestha, Sanjeet Krishna; Sharma, Rabin; Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2023)
BACKGROUND AND AIMS Severe acute pancreatitis can have serious consequences and a high mortality rate and may necessarily require intensive care unit admission. This study is to describe the demographic and clinicopathological characteristics of severe acute pancreatitis (SAP) in a tertiary-level intensive care unit (ICU). METHODS The study was designed retrospectively with a diagnosis of severe acute pancreatitis (SAP) admitted to the tertiary-level adult ICU “between” January 2019 to December 2022. RESULTS A total of 52 patients were enrolled in this study. The maximum numbers of patients were between 41 to 52 years of age, with a median age of 47.6 years. Gallstone (biliary) was identified as the most important etiological factor associated with severe acute pancreatitis. Among the known etiological factors, 52% of the cases were related to gallstone disease, 28.8% were due to alcohol, 7 (13.4%) to other causes (such as idiopathic, post-viral, post-ERCP, and drug-induced), and 5.7% were due to triglycerides. In our study, the most common symptoms were abdominal pain and vomiting. And the majority of patients recovered with conservative treatment. The majority 48 (92.3%) of patients improved, while 4 (7.6%) died. Eighteen (34.6%) patients required Mechanical ventilation (MV), while 10 (19%) with vasopressor supports. Eleven patients (21%) had evidence of an acute kidney injury on admission. Three patients (5.7%) underwent surgery, including necrosectomy and open cholecystectomy. The median length of ICU stay was 6.3 days. CONCLUSIONS The most common cause of severe acute pancreatitis was gallstone, followed by alcohol-related. SAP was seen more commonly in the male gender in the age group of 41-52 years. The most common presenting symptoms were abdominal pain and vomiting. Most SAP cases could be managed conservatively.